Satisfaction of Patients Regarding Health Care Services at Selected Upazila Health Complexes of Bangladesh (Journal of Preventive and Social Medicine, 2026)
Background: Hospitals are important vehicles for the delivery of health care services to the patients and feedback from patients in essential to measure the quality of care provided by health personnel. The study aims to determine the level of patient satisfaction in selected upazila health complexes of Bangladesh.Materials and methods: A descriptive cross-sectional study was conducted in 59 randomly selected UHCs across four Bangladeshi divisions from December 2023 to May 2024. Data were collected from 882 patients using a pre-tested semi-structured questionnaire. Patient satisfaction was assessed using the SERVQUAL framework to evaluate healthcare quality in the Bangladeshi context.Results: Among the respondents (patients), 66.2% were female and 82% were married. About 53.3% respondents were housewife and 33% had no formal education. Regarding easy to getting services, 77.6% were satisfied on waiting time in reception area, 79.8% in registration area and 78% in visit to doctor. Regarding interpersonal manner, 17.3% were dissatisfied on courtesy towards the doctor, 5.9% towards the nurses and 16.8% towards the staff.  About 89.1% patients were satisfied on doctors’ willingness, 87.2% on time taken to answer question, 79.1% on physical examination but only 54% satisfied on privacy arrangements. On the other hand, more than 86% were satisfied on explanation of illness, explanation of treatment, instruction regarding medication and follow-up. About 52.9% dissatisfied on facilities to safe drinking water supply, 57.5% about toilet facilities and 29.5% on overall cleanliness in the hospital. Among the respondents, 89.4% patients had average level of satisfaction in emergency department, 86.7% had average level in in-patient department and 89.3% had average level of satisfaction in out-patient department of the selected UHCs. Regarding overall satisfaction of UHCs, around 88.3% respondents had average level of satisfaction.Conclusion: This study revealed an average level of patient satisfaction with the services provided by the selected UHCs in Bangladesh. Improving cleanliness, safe drinking water, toilet facilities, investigation services, special public relation related training and privacy during examinations can significantly boost patient satisfaction in the Upazila Health Complexes.JOPSOM 2025; 44(1): 37-44